Extracellular Haloalkalophilic Pectinase Produced by Virgibacillus salarius Strain 434—A Useful Tool for Biotechnological Applications - Ivanka Boyadzhieva; Kaloyan Berberov; Nikolina Atanasova; Nikolay Krumov; Lyudmila Kabaivanova (Applied Sciences)
The interest in microbial pectinases is increasing due to their use in the biotechnological and food industries in response to global demand. In this study, among the 22 halophilic bacterial strains screened, 20 showed pectinase activity. The highest activity was measured for Virgibacillus salarius strain 434. As pectinase production meets many parameter optimization constraints, optimal production conditions for maximizing the yield of the pectinase synthesized using the investigated strain were followed. Enzyme purification was accomplished at up to 11.5-fold via ultrafiltration and gel filtration chromatography, until the enzyme’s specific activity had increased 10-fold (104.3 U/mg). The enzyme’s molecular weight was determined to be 68 kDa. Km and Vmax values of 0.38 mg/mL and 120 U/mg, respectively, were determined. The purified pectinase from Virgibacillus salarius strain 434 showed good thermal stability. A half-life of 20 min at 70 °C and high catalytic activity under haloalkaline conditions (pH 9 and 70 g L−1 NaCl) were observed. Its storage stability at −20 °C exceeded 2 months. This demonstrates its potential for application in industries where these extremes are present, as the harsh conditions in industrial processes require novel pectinases with unique properties instead of the use of hazardous chemicals.